La vertiente locutiva e elocutiva en la manipulación del referente en lengua inglesa. Los procesos mixtos: cuasieufemismo vs. cuasidisfemismo - Crespo Fernández, Eliecer (Estudios Ingleses de la Universidad Complutense, 2006)
When dealing with linguistic interdiction, traditional scholarship has focused on the processes in which the sense and reference of the utterance coincides with its communicative force either to perform its mitigating (euphemistic) or offensive (dysphemistic) function. However, not much ink has been spilled over those processes in which the locutionary act does not coincide with its illocutionary force in a given communicative context. The aim of this paper is to account for the linguistic behaviour of those utterances, as a discursive phenomenon, considered as “mixed processes of referent manipulation”. Under this name, we will analyze the special cases of referent manipulation, closely linked to euphemism and dysphemism, in its twofold and antithetical dimension: “quasieuphemism” and “quasidysphemism”.